2014
DOI: 10.1002/cbm.1918
|View full text |Cite
|
Sign up to set email alerts
|

Using social bonding theory to examine ‘recovery’ in a forensic mental health hospital: A qualitative study

Abstract: The first four themes map closely onto Hirschi's criminologically derived social bonding theory; however, indeterminacy of stay also arose as a common theme. In addition, the theory was too simple in its separation of elements; our data suggested the complex integration of themes. Our findings may be useful for informing evaluation of forensic mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 30 publications
(30 reference statements)
1
42
0
Order By: Relevance
“…Loneliness is common in forensic hospital settings [21, 33]. Interviews with patients revealed that patients’ families often think of them as a liability and are not willing to visit them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loneliness is common in forensic hospital settings [21, 33]. Interviews with patients revealed that patients’ families often think of them as a liability and are not willing to visit them.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not identify any previous studies that had been conducted on mentally ill offenders’ experiences and perceptions of long stay in forensic psychiatric hospitals in China. The interview schedule was developed based on previous qualitative studies from other countries (see Additional file 1) [18, 2126]. All interviews were conducted in a private meeting room in the hospital by graduate students studying forensic psychiatry.…”
Section: Methodsmentioning
confidence: 99%
“…Literature suggests that positive social relationships can have a significant impact on patient's recovery (Nijdam-Jones et al, 2015). Social cohesion has been the centre of government policies within mental health services, for example, No Health without Mental Health (DoH, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have now identified key principles of recovery as expressed by forensic mental health service users (e.g., Drennan & Aldred, ; Drennan & Woolridge, ; Livingston, ; Livingston, Nijdam‐Jones, Lapsley, Calderwood, & Brink, ; Nijdam‐Jones, Livingston, Verdun‐Jones, & Brink, ), including two reviews (Clarke, Lumbard, Sambrook, & Kerr, ; Shepherd, Doyle, Sanders, & Shaw, ). Clarke et al () conducted a systematic review and narrative synthesis of the 11 qualitative studies on offender‐patient perceptions of personal recovery, identifying six super‐ordinate themes: connectedness, sense of self, coming to terms with the past, freedom, hope, health, and intervention.…”
Section: Patient Experiences Of Secure Recoverymentioning
confidence: 99%
“…The importance of interpersonal connection as a facilitator of recovery is a strong and recurring theme among offender‐patients. In a study of 30 forensic inpatients, Nijdam‐Jones et al () found five major factors that were perceived as facilitating or hindering recovery: involvement in programmes, belief in rules and social norms, attachment to supportive individuals (family, friends, and staff), commitment to work‐related activities, and length of stay in hospital. By contrast, the stigma and isolation which may be associated with forensic hospitalisation were noted to disrupt these key attachments and, with uncertainty surrounding the length of hospital stay and associated feelings of hopelessness, potential impediments to recovery.…”
Section: Patient Experiences Of Secure Recoverymentioning
confidence: 99%